The Influence of Digital Marketing, Fear of Missing Out (FOMO), and Online Consumer Reviews on Purchase Decisions for Macpop Products in Surabaya - Feri Ardiansyah; Rizky Dermawan (Dinasti Publisher, 2024)
This research aims to determine the influence of digital marketing, fear of missing out (FoMO), and online consumer reviews on purchasing decisions for Macpop products in Surabaya. By using quantitative data analysis and appropriate methods, this research aims to provide deeper insight into the contribution of these factors in purchasing decisions for Macpop products in Surabaya. This research used a quantitative method involving 90 respondents selected by purposive sampling. Respondents consisted of Macpop consumers aged between 18 and 45 years. Data collection involved primary and secondary data, and analysis was carried out using the Partial Least Squares (PLS) technique with validity, reliability and hypothesis testing. The research results show that: (1) there is a significant and positive influence of digital marketing on the decision to purchase Macpop products, (2) there is a significant and positive influence of fear of missing out (FoMO) on the decision to purchase Macpop products, and (3) there is a significant and positive influence positive online consumer reviews regarding purchasing decisions for Macpop products.